Legal Responsibility of Land Deed Officials (PPAT) for the Making of Deeds with Legal Defects that are Detrimental to Land Owners Based on Court Decision Number 328/Pdt/2022/Pt Sby - Widodo, Wahyu; Arifulloh, Achmad (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
This study aims to analyze: 1)Legal responsibility of Land Deed Making Officials (PPAT) for making legally flawed deeds and harming landowners based on Court Decision Number 328/PDT/2022/PT SBY. 2) Legal implications of making legally flawed deeds by PPAT on the legal certainty of land ownership based on Court Decision Number 328/PDT/2022/PT SBY. This type of research is normative legal research. The approach method in this research is a case study approach and a statute approach. The type of data in this research is secondary data. The data collection method uses library techniques (study documents). The analysis in this research is qualitative. The results of the study concluded: 1) The legal responsibility of Land Deed Making Officials (PPAT) for making legally flawed deeds and harming landowners based on Court Decision Number 328/PDT/2022/PT SBY shows that PPAT has legal responsibility that stems from positive norms that regulate the authority of his position. Based on Hans Kelsen's theory of responsibility, a person can only be held legally responsible if proven to have violated a valid norm in a hierarchical legal system. In this case, the Surabaya High Court assessed that the Land Deed Official (PPAT) had carried out his duties according to the procedures stipulated in Government Regulation Number 24 of 1997, Government Regulation Number 37 of 1998 in conjunction with Government Regulation Number 24 of 2016, and Ministerial Regulation of ATR/BPN Number 2 of 2018, so that no violation of positive legal norms was found and there was no basis for imposing legal sanctions. Theoretically, the application of Kelsen's theory shows that the Indonesian legal system still emphasizes formal legality and has not fully accommodated substantive justice. 2) The legal implications of the creation of legally defective deeds by PPATs on the legal certainty of land ownership based on Court Decision Number 328/PDT/2022/PT SBY, namely showing that deeds that do not meet formal and material requirements have lost their evidentiary power as authentic deeds, create uncertainty about land ownership status, and undermine the function of land registration as an instrument of legal protection. A legally flawed deed can potentially revoke the certificate issued on its basis, giving rise to multiple disputes between the legitimate owner and a good-faith purchaser. This demonstrates that legal certainty in land matters depends not only on the administrative system but also on the professionalism and legal responsibility of the Land Deed Official (PPAT) as a public official.